Impact of wood species on microbial community composition, beer chemistry and sensory characteristics during barrel‐ageing of beer. (3rd December 2021) - Bossaert, Sofie; Winne, Valérie; Van Opstaele, Filip; Buyse, Jasper; Verreth, Christel; Herrera‐Malaver, Beatriz; Verstrepen, Kevin J.; De Rouck, Gert; Crauwels, Sam; Lievens, Bart
Summary: Barrel‐ageing of conventionally fermented beers is becoming increasingly popular in recent years, but only very little is known about the underlying process. In this study, we show that wood species significantly affects the bacterial community composition, beer chemistry and sensory characteristics throughout 38 weeks of barrel‐ageing. Whereas the microbial communities of oak‐ and acacia‐aged beer became dominated by Pediococcus damnosus and Brettanomyces bruxellensis, beer aged in oak barrels also contained a large fraction of Acetobacter sp. (29.34%) and to a lesser extent Paenibacillus sp. (2.74%) that were almost undetected in acacia‐aged beer. Oak barrels also imparted substantial concentrations of eugenol, lactones and vanillin, while acacia‐aged beer contained high concentrations of total polyphenols and β‐glucan, which also translated into different sensory perceptions. Altogether, our results provide novel insights into the barrel‐ageing process of beer, and may pave the way for a new generation of beers with a noteworthy flavour complexity. Abstract : A conventionally fermented beer was aged inside oak and acacia barrels for 38 weeks, and the microbial community composition, beer chemistry and sensory characteristics were assessed throughout the process. The microbial communities in both wood species became dominated by Pediococcus damnosus and Brettanomyces bruxellensis, but oak‐aged beer also contained a large share of Acetobacter sp. (29.34%), while this fraction was almost undetected in acacia‐aged beer. Oak barrels also imparted substantial concentrations of eugenol, lactones and vanillin, while acacia‐aged beer contained high concentrations of total polyphenols and β‐glucan, which also translated into different sensory perceptions.